Reverse brain drain: career aspirations of Malaysian repatriates - Ismail, Maimunah; Umar Baki, Nordahlia; Kamaruddin, Nor Ainun Yeop; Malik, Ashish (Universal-Publishers, 2016)
Purpose: This study investigates the influence of push and pull factors on career aspirations of Malaysian repatriates. Design/methodology/approach: The Social Cognitive Career Theory (SCCT) was used as the study’s underlying theory. Data were gathered from 129 self-initiated repatriates and analysed using multiple regression analysis. Findings: The analysis shows that political variables of push factors, as well as personal and family variables of pull factors, predicted repatriates’ career aspirations. The independent variables explained 31.2% variance of repatriates’ career aspiration model. Research limitations/implications: The research was limited to repatriates employed in organizations within the Klang Valley region, namely Kuala Lumpur, Putrajaya and Petaling Jaya. Practical implications: The paper offers practical implications for human resource managers, general managers, and employees by using the links between the predictive factors and career aspirations of repatriates to further strategize human resource development strategies. The findings could help government bodies to narrow their focus on repatriates’ needs so that the loss of talents due to brain drain would be repaid upon their return. As a result, repatriates will also be able to contribute their skills, expertise, knowledge and experiences that they have gained abroad to the homeland. Originality/value: This study is a step forward in understanding the influence of social, personal, family, economic and political factors on the career aspirations of repatriates. The study, the first of its kind in this country, provides an insight to human resource practitioners in dealing with the career aspirations of repatriates.